Ethical Deterioration in an Islamic Society its Causes and Solution - Dr. Syed Asif Mahmood; Dr.Shah Junaid Ahmed Hashmi (jihat-ul-islam, 2022)
This paper attempt to examine ethical deterioration in an Islamic society and its causes and solution from the Islamic perspective. Nowadays, Muslims are undergoing moral deterioration, especially Muslim youth are not aware of Islamic ethics and morals. Therefore, embracing Islamic ethics have become important for Muslims. In fact, there are many factors and causes that lead towards moral decline and ethical deterioration in Muslims. For example, lack of appropriate upbringing in the Muslim family system, unawareness of parents about children’s issues, breaching of peer relations by parents, lack of good and model character in the homes, ignorance about the concept of good and bad, less emphasis of preachers on socialization of people, spreading of brutality and adultery, and indulgence of people into wickedness. This study will be conducted from the verses of the Holy Qur’an and Ahadith of the Prophet (peace be upon him). This paper provides a detailed discussion about the causes and factors of ethical deterioration and moral decline. Furthermore, the paper presents a possible solution from an Islamic perspective. This endeavor will be beneficial for the improvement of ethical conditions of Muslims in an Islamic society.